Correlation analysis of pathological manifestations on facades of box buildings: case study in Jaboatão dos Guararapes-PE - Silva, Rayssa Valéria da; Saruhashi, Mariana Lissa; Monteiro, Eliana Cristina Barreto; Soares, Willames de Albuquerque; Vasconcelos, Bianca M. (National Journal of City Management, 2025)
Objective – Identify and analyze the pathological manifestations on box buildings with painted coatings facades, as well as carry out a correlation analysis to understand the relationships between these structural problems.Methodology – The methodology adopted included detailed visual inspections, creation of damage maps, adhesion testing and statistical correlation analysis.Originality/Relevance – Identification of pathological manifestations through the execution of a damage map and data analysis using statistics, verifying their normality, representativeness of their averages and the correlation between the manifestations.Results – The results revealed the spatial distribution of pathological manifestations, highlighting critical areas and significant deterioration patterns.Theoretical/Methodological Contributions – The correlation analysis allowed us to understand the interactions between the variables studied, showing that the correlation between cracking and spalling, for example, indicates that cracks appear before spalling, proving the visual analysis and serving as an early warning to residents.Social and Environmental Contributions – The detailed analysis of pathological manifestations and the application of statistical tests are fundamental to guide maintenance and conservation actions, aiming to preserve the architectural heritage and the well-being of local communities.
Keywords: Pathological manifestations; Damage map; Box building; Correlation analysis